(untitled) (Leviathan (São Paulo), 2011)
This paper seeks to address the conceptual relationship between ‘Republic’ and ‘Personal Power’ to understand its implication in the debate on republicanism in Latin America. To this end, we will analyze the presidential figure in Alberdi as a specific form of implementing “neutral power” in the Argentine Republican tradition.This work presents two ways to develop this interpretative hypothesis. The first one is an analysis of a textual corpus of Alberdi made up of youth, maturity and posthumous texts. This will help us question the conceptual relationships between "Monarchy" and “Republic” using the heuristic tools that the History of Concepts has brought to Political Theory.The second way (and main thread of this work), is to assume that the presidential figure in Alberdi is a neutral power. To this end, and contrary to the traditional Latin American constitutionalism readings that only accept this possibility in the case of the Brazilian imperial Constitution of 1824, we will present a re-reading of the ways neutral power appears in the production of Benjamin Constant. This will be done from the perspective of the readings that Carl Schmitt does of the French liberal tradition; ones that make him suggest that a plebiscitary President could be an incarnation of the neutral power for the Weimar Republic.Our reading returns to the presidential figure in Alberdi without fear of falling into anachronism, not only because it is an anchor point to tensions between “Republic” and “monarchy” but also because it is an original form of appropriating Benjamin Constant’s notion of ‘neutral power’. And this originality is not only due to its influence in the Argentine Constitution of 1853, but also to the fact that the conceptual and political dilemmas posed by it are updated in modern Argentina, where personal power is a key element in politics, even in the most heavily Republican form.